Failure of the international intervention in refugee crisis Lebanon. (c2015) - Francis, Youssef Charbel (2015)
..”During wartime, people still dream, fall in love, aspire - they are human, they are not freaks”… The Art of War The issue of refugees holds within it several aspects of the study of international affairs including human rights, politics, power, war, international intervention, foreign policy, domestic policies, policy making, demography and ethnicity. My work experience with the United Nations High Commissioner for Refugees (UNHCR) in Lebanon has encouraged me to deepen my knowledge on this issue and make use of my observations during my work, which are the result of daily field interaction with the Iraqi, Syrian, Sudanese and other refugees from different nationalities who fled their country seeking safe heaven and a life with dignity in Lebanon. The aim is to explore the roots and causes of the continuous suffering of refugees in Lebanon based on my personal experience as well as the national and international surveys and studies. This study will make use of the literature review on this subject and apply the theoretical findings on the case of Lebanon. Through analyzing the various aspects of the refugee crisis in Lebanon, this paper has discovered that the gap in the international refugee law has allowed the political considerations of the national and international actors to contribute to increased refugee suffering. Particularly, this paper argues that the international law is weak and lacks adequate implementation mechanisms that are essential to induce the international community and the national governments to provide adequate protection for refugees.